Rekonstruksi Kedudukan Dewan Perwakilan Daerah Setelah Putusan Mahkamah Konstitusi No. 79/PUU-XII/2014 - Mirja Fauzul Hamdi (Universitas Syiah Kuala, 2018)
Keberadaan DPD yang diatur berdasarkan Undang-Undang No. 17/2014 masih dinilai diskriminatif dalam pelaksanaan kewenangan, khususnya bidang legislasi dibandingkan dengan Dewan Perwakilan Rakyat. Upaya pengujian undang-undang dilakukan oleh DPD ditujukan guna menjamin kemandirian lembaga sebagaimana amanah Undang-Undang Dasar Tahun 1945. Berdasarkan Putusan Mahkamah Konstitusi No. 79/PUU-XII/2014 merupakan suatu bentuk rekonstruksi hukum yang dijadikan sebagai dasar hukum bagi DPD dalam menjalan kewenangan bidang legislasi. Reconstruction of Regional Representative Council after the Decission of Constitutional Law No. 79/PUU-XII/2014 The existence of The Regional Representative Council that regulated by Law No. 17/2014 remain discriminative in exercising their authority, particulary in legislative function and compare to the House of representative. The Regional Representative Council has conducted a legal review to ensure the independency of it institution as regulate by Constitution 1945. Based on the decission of the Constitutional Court No. 79/PUU-XII/2014 as the legal standing for DPD in exercising their legislative authority.